Gender and Governance Issues in Local Government (Patan Pragya, 2021)
This article based on issues related to gender and good governance on Local Government. The main aims of the article is to find out the issues of gender and good governance on Local Government in Nepal. That means, reducing poverty requires considerable efforts to improving the participation of women, the poor and back-warded people on local governance and they also participated for resource distribution and mobilization. This article is based on cross sectional descriptive and analytical types of research design. Descriptive research aims are to accurately and systematically describe population, situation or phenomenon. It can answers what, where, when and how questions, but not why questions. It can use a wide variety of research methods to investigate one or more variables. These out- comes suggest that (i) empowering the poor through good governance will expand their economic opportunities and increase their inclusion in the social life of their communities and (ii) the project’s framework and approach could be mainstreamed into Nepalese government efforts to promote good governance and to reduce poverty at the grassroots level. The public sector service deliveries are effectively conducted. The unique framework that applied for three pillars at the grassroots level. They are resources included employment opportunities, training programs and social sector programs. Nepalese law enforces the reserve seats for women in local governments, but traditionally of gender inequality and patriarchal values have limited the participation and effectiveness of female representatives. It also affect the interface among women representatives, government officials, and poor constituents with social mobilization and capacity building to improve the effectiveness of women representatives and empower them to represent their poor constituents and deliver the services and opportunities they so desperately need. Capacity building provided they require knowledge, skills, and techniques to women representatives, and local resources were mobilized for their poorest constituents. The fact that a majority of the women representatives were themselves deprived that the Training and support.